Electronically Excited States of Potential Interstellar, Anionic Building Blocks for Astrobiological Nucleic Acids - Santaloci , Taylor J.; Strauss , Marie E.; Fortenberry , Ryan C. (Frontiers in Astronomy and Space Sciences, 2021)
Functionalizing deprotonated polycyclic aromatic hydrocarbon (PAH) anion derivatives gives rise to electronically excited states in the resulting anions. While functionalization with −OH and −C2H, done presently, does not result in the richness of electronically excited states as it does with −CN done previously, the presence of dipole-bound excited states and even some valence excited states are predicted in this quantum chemical analysis. Most notably, the more electron withdrawing −C2H group leads to valence excited states once the number of rings in the molecule reaches three. Dipole-bound excited states arise when the dipole moment of the corresponding neutral radical is large enough (likely around 2.0 D), and this is most pronounced with the hydrogen atom is removed from the functional group itself regardless of whether functionalized by a hydroxyl or enthynyl group. Deprotonatation of the hydroxyl group in the PAH creates a ketone with a delocalized highest occupied molecular orbital (HOMO) unlike deprotonation of the ring where a localized lone pair on one of the carbon atoms serves as the HOMO. As a result, hydroxyl functionlization and subsequent deprotonation of PAHs creates structures that begin to exhibit structures akin to nucleic acids. However, the more the electron withdrawing the functional group, the more electronically excited states are present implying that such anions will be stabilized in the harsh conditions of the interstellar medium.